2009
DOI: 10.1037/a0014894
|View full text |Cite
|
Sign up to set email alerts
|

Attachment theory, childhood mistreatment, and religiosity.

Abstract: Guided by attachment theory, the authors explore the relationship of verbal, physical, and sexual mistreatment to attachment to God, as well as to concepts of God. Each form of mistreatment was related adversely to the religiosity measures. Attachment to parents mediated the relationship between two maltreatment variables (verbal and physical mistreatment) and attachment to God, as well as the concept of God as loving and as distant. However, attachment to parents did not mediate the relationship between attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 46 publications
6
39
3
6
Order By: Relevance
“…as loving, controlling, or distant), which have often been used in studies of the association between maltreatment and religiosity (e.g. Kane et al, 1993;Reinert & Edwards, 2009). Perhaps childhood maltreatment has stronger effects on some aspects of religiosity than others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…as loving, controlling, or distant), which have often been used in studies of the association between maltreatment and religiosity (e.g. Kane et al, 1993;Reinert & Edwards, 2009). Perhaps childhood maltreatment has stronger effects on some aspects of religiosity than others.…”
Section: Discussionmentioning
confidence: 99%
“…religious participation, importance of religion, stability of religious affiliation, religious doubts, and images of God). Findings of these studies have been mixed, with most showing decreased religiosity among abuse victims (Bierman, 2005;Finkelhor, Hotaling, Lewis, & Smith, 1989;Hall, 1995;Kane, Cheston, & Greer, 1993;Reinert & Edwards, 2009) (Kennedy & Drebing, 2002;Lawson, Drebing, Berg, Vincellette, & Penk, 1998;Reinert & Smith, 1997).…”
Section: Please Scroll Down For Articlementioning
confidence: 93%
See 1 more Smart Citation
“…An individual's relationship to God is indeed not only an attachment in itself but a reflection of one's IWM of attachment, often uniquely affected in the case of CSA (Alexander, 1992;Brokaw & Edwards, 1994). Quite notably, a recent study broadly examining child maltreatment (physical, verbal, sexual) found that individuals who reported higher levels of sexual abuse than other forms of maltreatment showed a more insecure attachment to God (Reinert & Edwards, 2009). CSA investigators are strongly encouraged to build on this contribution by allowing attachment theory to guide their future research and hypotheses.…”
Section: Theoretical Recommendationsmentioning
confidence: 95%
“…El apego a Dios en el que los individuos perciben a Dios como un ser benevolente y emocionalmente accesible o "seguro", funciona como un factor de protección que reduce los niveles de ansiedad (Bradshaw, Ellison & Marcum, 2010;Miner, 2009); también con mujeres jóvenes en riesgo para desórdenes alimentarios (Homan and Boyatzis, 2010) o en pacientes que sufren de dolor crónico (Dezutter, Luyckx Schaap-Jonker Büssing, Corveleyn and Hutsebaut, 2010), mientras que un apego "inseguro" a Dios correlaciona con mayor ansiedad, mayor riesgo en conductas asociadas con desórdenes alimentarios o niveles de dolor en pacientes médicos. Como es de esperar, poblaciones con trauma familiar tienden a experimentar a Dios desde la "inseguridad" (Reinert and Edwards, 2009).…”
Section: La Psicología Del Desarrollo Del Apego (Attachment) Con Diosunclassified